2015
DOI: 10.1038/srep08092
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced Activation of Glutathione Metabolic Pathways Suggests Potential Involvement in Plant Defense against the Gall Midge Mayetiola destructor in Wheat

Abstract: Glutathione, γ-glutamylcysteinylglycine, exists abundantly in nearly all organisms. Glutathione participates in various physiological processes involved in redox reactions by serving as an electron donor/acceptor. We found that the abundance of total glutathione increased up to 60% in resistant wheat plants within 72 hours following attack by the gall midge Mayetiola destructor, the Hessian fly. The increase in total glutathione abundance, however, is coupled with an unbalanced activation of glutathione metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 45 publications
(71 reference statements)
3
27
0
1
Order By: Relevance
“…Furthermore, GR activity was enhanced in the terminal and median leaves, but remained nearly unchanged in the groups treated with Pb alone and in combination with GSH. Previously, it was also observed that GSH levels were increased during stress conditions, but GR activity remained unchanged, pointing to the GSH de novo synthesis (Liu et al, 2015). In current study, Pb contents and GSH concentrations in terminal and median leaves and primary and secondary roots were also measured (Figure 2).…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, GR activity was enhanced in the terminal and median leaves, but remained nearly unchanged in the groups treated with Pb alone and in combination with GSH. Previously, it was also observed that GSH levels were increased during stress conditions, but GR activity remained unchanged, pointing to the GSH de novo synthesis (Liu et al, 2015). In current study, Pb contents and GSH concentrations in terminal and median leaves and primary and secondary roots were also measured (Figure 2).…”
Section: Discussionsupporting
confidence: 70%
“…Flavonoid and tyrosine ammonialyases play important roles in plant defence early during infection [43]. In addition, glutathione and some unsaturated fatty acids were also participates in signaling of plant defense against biotic and abiotic stresses [44]. These results indicated that these four pathways may play important role for ability of Jiangcheng 3A resistance T.…”
Section: Key Pathway Resistance To T Horrida In Ricementioning
confidence: 90%
“…In other words, despite a stable level of GSH, a dramatic increase in GST activity may indicate undisturbed usage and recycling of GSH. Associatively, possible alternative pathways to convert GSSG back to GSH through class III peroxidases have been suggested due to uncorrelated results between GR and glutathione peroxidase in wheat (Liu et al, 2015).…”
Section: Primer Namementioning
confidence: 99%